Current Scenario of Indian Green Marketing and Exploring the Challenges: Exploring the Future of Sustainable Marketing Practices in India (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In this global age, preserving our natural world is the greatest obstacle. Consumers change their behaviour and habits with the aim of maintaining a clean and sustainable atmosphere because of the increased knowledge of different environmental concerns. Corporations and organisations, through investing in environmentally conscious corporate practises, often aim to keep up with this change in the customer attitudes to achieve comparative advantages. Green marketing has now emerged as a relevant phenomenon, both in India and around the world. Quite modern marketing is, though, one of the fastest rising segments of the marketing principle. green marketing is This paper underlines the value of green marketing, its future in future years, and how businesses benefit from green marketing practises.